Some studies of the chemistry and technology of soupfin shark liver oil - Lategan, Andries Willem; Lategan, Andries Willem (Department of Chemistry, 2017)
During the past ten years the world demand for vitamin A has increased steadily. The increase is due partly to growing popularity of vitamin therapy and partly to the enormous rate at which vitamin A is being used in America for animal feeding. During the war years it has been used extensively for food fortification in England and Europe, and this will probably be continued for several years. It is very difficult to estimate the annual world consumption of vitamin A, but we know that in America 67 x 10¹² International Units (I. U.) were used in 1939. Approximately 60% of this quantity was used for animal feeding. We also know that in England the fortification of margarine is compulsory and that the diet of all school children is supplemented with vitamin A. The distribution of the world production of vitamin A was seriously disrupted by the war, when the Norwegian and Japanese productions were cut off from their normal destinations. Under these circumstances it is no wonder that the United States, Canada, South Africa, India and Australia made serious and successful attempts to produce fish liver oils, the main source of vitamin A. Argentina produced 25 x 10¹² U.S.P. units in 1945 and the United States 9 x 10¹³ U.S.P. units in the same year. The South African production increased from 2 x 10¹² I.U., valued at £80,000 in 1943, which year may be regarded as the birth of the South African industry, to 1 x l0¹³ I.U., valued at £400,000 in 1946-1947. There are four companies engaged in the production of fish liver oils in South Africa, and the success of this venture has probably provided the biggest impetus to our rapidly expanding fishing industry. This treatise deals with some aspects of the composition, characteristics, production, refining and storage of soupfin shark liver oil.